Hemorrhoidectomy Using (10600 nm) CO2 Laser - Awazli, Lutfi G. (Iraqi Journal of Laser, 2019)
Hemorrhoids are one of the most common surgical conditions. The hemorrhoid may cause symptoms that are: bleeding, pain, prolapse, itching, spoilage of feces, and psychologic discomfort. There are many methods for treatment of hemorrhoid like, medical therapy, rubber band ligation, electerocoagulation, stapled hemorrhoidpexy, photocoagulation, sclerothereapy, doppler guided artery ligation, Cryosurgery, and surgery. All methods for treatment of hemorrhoids have advantages, disadvantages, and limitations. Conventional haemorrhoidectomy was the traditional operation for the treatment of hemorrhoids. But recently other modalities of treatment had been used as an alternative operations including CO2 laser haemorrhoidectomy. This work aims to evaluate the efficacy of CO2 laser for treatment of hemorrhoids. This study was carried out on 25 patients complaining from symptomatic hemorrhoids for many years. Laser hemorrhoidectomies were done for them in Baghdad City for a period of one year. There were 19 males (76%) and 6 females (24%) with age range of 25-65 years. The laser used in this procedure is CO2 laser (10600nm) continuous wave mode and non-contact method. Patients were discharged home and were followed for 4 months for healing progress and complications. The following criteria are taken in consideration for assessment: (Pain, Bleeding, Infection, Ambulation, Anal stenosis, Incontinence, Recurrent). All cases were treated as day case. 18 patients (72%) underwent laser hemorrhoidectomy under spinal anesthesia while other 7 patients (28%) under general anesthesia. The operative time ranged from 10 to 30 minutes with an average of 22minutes. The postoperative hospital stay ranged from 3 to 9 hours. Only few of cases showed complication after treatment by CO2 laser. No pain (64%), mild to moderate pain (28%), severe in (8%), Mild Bleeding occurred in 3 cases (12%), infection: only 2 patients (8%), retention of urine: four patients (16 %), mild anal stenosis 3 patients (12 %), Mild temporal incontinence occurred in 2 patients (8%), and recurrence zero. It is concluded that CO2 laser hemorrhoidectomy is a safe and effective procedure associated with low incidence of post-operative complications.